Pilomatricoma With Bullous Appearance: A Case Report - Yue-Ying Fan; Jin-Fu Li; Ying-Jun Su; Chi-Yu Jia (Wolters Kluwer Health, 2023)
Introduction:. Pilomatricoma is usually a solitary, deep dermal firm nodule with an overlying normal epidermis. Bullous pilomatricoma is rarely reported; thus, its pathogenesis has not been elucidated. We report a case presenting the pilomatricoma with bullous change. Case presentation:. A 19-year-old female presented a firm nodule covered by a bulla on her right upper arm. Histopathological examination showed the tumor was composed of basophilic basal-like cells and shadow cells. No cellular atypia or abnormal mitotic figures were observed. All these clinical characteristics and pathological results point to the diagnosis of bullous pilomatricoma. The tumor was surgically removed by enlargement. Discussion:. We hypothesize that a history of trauma and rapid growth may contribute to the diagnosis of the bullous pilomatricoma. The appearance of the bullous can be explained by the dilated lymphatic vessels seen in histopathologic examination. We give a case report help clinicians to better diagnose this entity and decrease the rate of misdiagnosis. Conclusion:. We observed a rare bullous variant of pilomatricoma. Hence, when identifying a patient of bullous pilomatricoma, a detailed medical history and physical examination are essential.